2018
DOI: 10.14419/ijet.v7i3.12.15858
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Mechanical and Microstructural Properties of Concrete with Agro-Waste

Abstract: Due to ever-increasing disposal problems of agricultural wastes in developing countries have created opportunities for use of agricultural wastes in the construction industries. An attempt has been carried out by partial replacement of cement with areca-nut shell, fine aggregate with coconut shell powder by pulverizing it into ashes and coarse aggregate with oil palm shell9. Concrete specimens were cast and cured for 28 days, a detailed comparison is made with conventional concrete and concrete with agrowaste … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Mainly because these bio-based products meet the properties and performance requirements for building materials. In addition, they are similar to commercial products and conform to regulatory specifications [5, 18, To improve the properties and/or guarantee the performance of most of the bio-based products in Table 1, studies suggest substitution percentages between 5 and 15% by weight of AWBs [6,16,18,19,21,25,33,50,51,53,66,69,77,90,100,103,115]. These findings align with a study that identified similar percentages, between 5 and 10% AWB for fired clay bricks [100].…”
Section: Main Types and Properties Of Awbs Used By Categorysupporting
confidence: 73%
See 1 more Smart Citation
“…Mainly because these bio-based products meet the properties and performance requirements for building materials. In addition, they are similar to commercial products and conform to regulatory specifications [5, 18, To improve the properties and/or guarantee the performance of most of the bio-based products in Table 1, studies suggest substitution percentages between 5 and 15% by weight of AWBs [6,16,18,19,21,25,33,50,51,53,66,69,77,90,100,103,115]. These findings align with a study that identified similar percentages, between 5 and 10% AWB for fired clay bricks [100].…”
Section: Main Types and Properties Of Awbs Used By Categorysupporting
confidence: 73%
“…Thirty-five percent of total European Union (EU) waste generation is in the construction sector [1]. In many countries, the management and disposal of waste from these sectors poses a serious problem, mainly from an environmental and social point of view [5,6].…”
mentioning
confidence: 99%
“…The rice husk ash is found effective as a replacement for sand up to 10% [9]. The presence of CSH gel and Ca (OH)2 in concrete with addition to the agro-waste attributed to greater strength and other properties in comparison with conventional concrete for lesser content of agro-waste [10]. Utilization of RHA and Bagasse Ash in Self Compacting Concrete (SCC) resulted in the densification of the microstructure of concrete due to the filler effect and secondary CSH gel formation by pozzolanic reaction [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated the suitability of agricultural waste for use in concrete as a substitute for cement, ne, and coarse aggregates . It follows that using agricultural waste materials would contribute to eliminating the problem of pollutants and reduce construction materials' costs (Antony Godwin et al, 2018). It is possible to partially replace cement with ashes produced from the combustion of Pigeon pea stalks to fabricate sustainable concrete.…”
Section: Introductionmentioning
confidence: 99%